Current workload recommendations in baseball pitchers: A systematic review - Bakshi, N. K.; Inclan, P. M.; Kirsch, J. M.; Bedi, A.; Agresta, C.; Freehill, M. T. (The American Journal of Sports Medicine, 2020)
Background: Several recommendations have been made regarding pitch counts and workload for baseball players of different levels, including Little League, high school, collegiate, and professional baseball. However, little consensus is found in the literature regarding the scientific basis for many of these recommendations. Purpose: The primary purpose of this study was to summarize the evidence regarding immediate and long-term musculoskeletal responses to increasing pitching workload in baseball pitchers of all levels. A secondary purpose of this review was to evaluate the extent to which workload influences injury and/or performance in baseball pitchers. Study Design: Systematic review. Methods: We performed a systematic search in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for studies addressing physiologic and/or pathologic musculoskeletal changes in response to a quantifiable pitching workload. We included studies examining the effects of pitching workload on performance, injury rate, and musculoskeletal changes in Little League, high school, collegiate, and professional baseball players. Results: We identified 28 studies that met our inclusion and exclusion criteria: 16 studies regarding Little League and high school pitchers and 12 studies regarding collegiate and professional pitchers. The current evidence presented suggests that increased pitching workload may be associated with an increased risk of pain, injury, and arm fatigue in Little League and high school pitchers. However, little consensus was found in the literature regarding the association between pitching workload and physiologic or pathologic changes in collegiate and professional pitchers. Conclusion: Evidence, although limited, suggests the use of pitch counts to decrease injury rates and pain in Little League and high school baseball pitchers. However, further research must be performed to determine the appropriate number of pitches (or throws) for players of different ages. This systematic review reported conflicting evidence regarding the use of pitch counts in college and professional baseball. Future high-quality research is required to determine the role, if any, of pitch counts for collegiate and professional pitchers.